Enhancing Competitiveness For Employee Performance In The Hospitality Sector: An Analysis Of Core Self-Evaluation And Proactive Personality - Iis Azelya; Indah Noviyanti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
The hospitality sector in Bangka Island has experienced significant growth, with an increasing number of both star-rated and non-star hotels. In the face of intense industry competition and ongoing digital transformation, employee performance becomes a crucial element in maintaining service quality and customer satisfaction. This study aims to analyze the influence of core self-evaluation and proactive personality on hotel employee performance in Bangka Island. A quantitative descriptive approach was used, involving the entire hotel population as the research sample. Data were collected through questionnaires and analyzed using partial least squares. The findings indicate that core self-evaluation has a positive influence on employee performance. Similarly, proactive personality also has a positive effect on hotel employee performance. These results suggest that an individual’s confidence in their self-worth, ability to face challenges, and tendency to act proactively are important factors in improving job performance. This study contributes theoretically to the literature on human resource management and offers practical implications for hotel management in designing employee development and management strategies that are more effective and aligned with individual personality traits.